A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Discovery and engineering of a compost-derived thermophilic BHETase for enhanced depolymerization of post-consumer PET - Xiaoli Zhou; Xian Li; Yi Zang; Lian Zhou; Guangda Feng; Ming-Rong Deng; Honghui Zhu (Journal of Hazardous Materials, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Case study of aircraft icing in-cloud measurements and explicit supercooled water prediction in Eastern China - Liping Luo; Ming Xue; Xin Xu; Lin Deng; Junxia Li; Rong Zhang (Atmospheric Research, 2026)

Hydrogeophysical Imaging and Joint Interpretation of Rainfall Infiltration on an Embanked Slope in the Mid-Lower Yangtze Hilly Region - Rong-wen Guo; Chen-yang Li; Zhuo Liu; Deng-kang Wang; Ming Yu (Applied Geophysics, 2026)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

An electrochemical reactor that enables continuous and uniform flow of high-viscosity slurry for semi-solid flow batteries - Chao Deng; Xiaoxin Li; Furong Xie; Miguel A. Modestino; Mustafa Kemal Bayazit; Barun Kumar Chakrabarti; Jeffrey Gostick; Zinan Wu; Rong Chen; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Phylogeography of a Small Mammal ( Blarinella quadraticauda ) Distributed Around the Sichuan Basin, Southwest China - Qing Liu; Yu Deng; Rong‐Hui Fan; Chang‐Kun Fu; Xu‐Ming Wang; Shao‐Ying Liu; Shun‐De Chen (Zoologica Scripta, 2025)
The rapid climatic fluctuations and geographical factors during the Quaternary glacial period, particularly in the Pleistocene epoch, play a pivotal role in shaping intraspecific genetic diversity. We conducted an investigation into the genetic structure and speciation mechanisms of a small mammal species, Asiatic Short‐Tailed Shrew ( Blarinella quadraticauda ), which is mainly distributed in the mountains surrounding the Sichuan Basin and its adjacent regions in southwest China. Extensive sampling was conducted across the region (180 Asiatic Short‐Tailed Shrews from 67 sites), followed by principal component analysis and discriminant analysis on complete skull data. Phylogenetic analyses were conducted using mitochondrial (Cytb) and nuclear (APOB and BRCA1) genes. Additionally, the potentially suitable distribution range under both current and historical climatic conditions was projected. Our results show that B. quadraticauda in the Sichuan Basin is divided into six major clades, which are largely morphologically similar, except for the clade from Baoxing, Sichuan, which exhibits a slightly larger size. Additionally, the species exhibits a nearly ring‐like distribution around the Sichuan Basin. Genetic exchange among populations in the northern and eastern regions of the basin appears to be limited, suggesting potential barriers to gene flow. Under the influence of the basin's lowlands, the rapid climate oscillation of the Quaternary glacial period and the uplift of the Tibetan Plateau, the species appears to have formed a ring distribution in the Sichuan Basin. Moreover, we have also updated the taxonomy and distribution range of B. quadraticauda .

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

An energy-saving pH-asymmetric electrolyzer for simultaneous methane conversion and hydrogen production - Rong Chen; Furong Xie; Zinan Wu; Xiaoxin Li; Chao Deng; Zhenpeng Yao; Guo-Ming Weng (Science Bulletin, 2025)

Parerythrobacter aurantius sp. nov., a Member of the Family Erythrobacteraceae Isolated from a Coastal Breakwater Stone - Yang Liu; Tao Pei; Juan Du; Ming-Rong Deng; Honghui Zhu (Current Microbiology, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Synergetic “amine scissors” break down cured epoxy resins with nearly 100% degradation efficiency - Furong Xie; Rong Chen; Chao Deng; Xiaoxin Li; Huiyan Yang; Yu Xie; Song Wang; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Versatile room temperature phosphorescence polymer with luminophore content as low as 0.05 wt% - Wen Wen Deng; Ze Ping Zhang; Min Zhi Rong; Ming Qiu Zhang (Chemical Engineering Journal, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

Design of a dual-responding genetic circuit for high-throughput identification of L-threonine-overproducing Escherichia coli - Buli Su; Peixuan Lai; Ming-Rong Deng; Honghui Zhu (Bioresource Technology, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Responses of Bacillus sp. under Cu(II) stress in relation to extracellular polymeric substances and functional gene expression level - Ling-ling Wang; Zheng-yan Yin; Yun Xu; Miao-yu Deng; Kai-ming Zhang; Quan Wang; Rong-ping Chen; Lei Yu (Environmental Science and Pollution Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Flavobacterium proteolyticum sp. nov., isolated from aquaculture water - Juan Du; Yang Liu; Tao Pei; Anzhang Li; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

Croceicoccus gelatinilyticus sp. nov., isolated from a tidal flat sediment - Tao Pei; Yang Liu; Juan Du; Kunpeng Huang; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

Inhella proteolytica sp. nov. and Inhella gelatinilytica sp. nov., two novel species of the genus Inhella isolated from aquaculture water - Yang Liu; Tao Pei; Juan Du; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2021)

Qipengyuania soli sp. nov., Isolated from Mangrove Soil - Yang Liu; Tao Pei; Ming-Rong Deng; Honghui Zhu (Current Microbiology, 2021)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Sphingomonas gimensis sp. nov., a novel Gram-negative bacterium isolated from abandoned lead–zinc ore mine - Guang-Da Feng; Song-Zhen Yang; Yong-Hong Wang; Guo-Zhen Zhao; Ming-Rong Deng; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2014)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Granaticins and their biosynthetic gene cluster from Streptomyces vietnamensis: evidence of horizontal gene transfer - Ming-Rong Deng; Jun Guo; Xiang Li; Chun-Hua Zhu; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2011)

Promoter Analysis of Mouse Scn3a Gene and Regulation of the Promoter Activity by GC Box and CpG Methylation - Guang-Fei Deng; Jia-Ming Qin; Xun-Sha Sun; Zu-Ying Kuang; Tao Su; Qi-Hua Zhao; Yi-Wu Shi; Xiao-Rong Liu; Mei-Juan Yu; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Journal of Molecular Neuroscience, 2011)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Effect of SPLUNC1 protein on the Pseudomonas aeruginosa and Epstein-Barr virus - Hou-De Zhou; Xiao-Ling Li; Gui-Yuan Li; Ming Zhou; Hua-Ying Liu; Yi-Xing Yang; Tan Deng; Jian Ma; Shou-Rong Sheng (Molecular and Cellular Biochemistry, 2008)

Timing and duration of supergene mineralization at the Xinrong manganese deposit, western Guangdong Province, South China: cryptomelane 40Ar/39Ar dating - Jian-Wei Li; Paulo Vasconcelos; Wei Zhang; Xiao-Dong Deng; Nurdan Duzgoren-Aydin; Dai-Rong Yan; Jian-Qiang Zhang; Ming-An Hu (Mineralium Deposita, 2007)